Mapping the intellectual landscape of VR-supported English learning: trends, gaps, and research frontiers - Ulzhan N. Urazaliyeva; Gulzhaina K. Kassymova; Meiramgul Yesbossyn (Scientific English, 2026)
Despite the growing body of literature and the increasing interest in virtual reality-assisted English learning, a comprehensive understanding of the key research clusters, influential studies, and existing gaps within this field remains scarce. This study aims to map the scholarly landscape of VR-supported English learning through a bibliometric co-citation analysis of publications indexed in the Scopus database between 2020 and 2026. Using the PRISMA framework, 56 relevant studies were selected and analyzed with VOSviewer and Litmaps to identify influential authors, collaboration patterns, keyword co-occurrences, and thematic clusters. The results revealed major themes related to higher education, learner motivation, willingness to communicate, intercultural competence, vocabulary acquisition, and immersive experiences. However, there are insufficient longitudinal studies, limited research on the inclusive aspects of VR-assisted language learning, and underexplored new VR types, such as XR, the Metaverse, and AI-enhanced VR applications. The study provides a roadmap for researchers and English instructors seeking to integrate VR technology into teaching.